Peran Makanan Laut Sumber Protein dan Anak Stunting di Wilayah Pesisir - Nirmala, Intan Ria; Octavia, Lestari (Poltekkes Kemenkes Kendari, 2022)
This paper explains the importance of using local food from sea catch fish in Southeast Sulawesi as a source of protein and its relation to reducing stunting prevalence in children. The article's source is a literature review related to seafood and stunting in children. This study explains the shift in children's eating patterns, barriers to consuming seafood as a protein source and promoting seafood as a protein source into a sustainable nutrition program. Multisectoral cooperation will aid in reducing the prevalence of malnutrition in vulnerable groups. Recognizing local resources that can be optimized as sources of food intake for vulnerable groups is also a must to be included in program preparation. This paper is confirmed by the results of ongoing studies and observations to help ensure the right program design to reduce stunting in coastal areas.